Serological classification of Neisseria gonorrhoeae with monoclonal antibody coagglutination reagents. - Coghill, D V (1987)
A total of 357 clinical isolates of Neisseria gonorrhoeae from 286 patients were classified serologically using two independently developed panels of monoclonal coagglutination reagents. The Pharmacia (Ph) Diagnostics panel comprised 14 reagents, five specific for serogroup WI strains and nine specific for serogroup WII/III strains, whereas the Genetic Systems (GS) panel comprised 14 reagents, seven specific for serogroup WI strains and seven specific for serogroup WII/III strains. Serogroup WI represented 45% and WII/III represented 55% of the patients. Using the monoclonal antibody reagents, the serogroups could be further subdivided into so-called serovars. The Ph reagents identified four WI serovars and 21 WII/III serovars, whereas the GS reagents identified 10 WI serovars and 18 WII/III serovars. By combining the results obtained with each panel, 15 Ph/GS WI serovars and 33 Ph/GS WII/III serovars were recognised. In the WI isolates, one predominating serovar was recognised, whereas in the WII/III isolates, no single serovar predominated and a much greater variety of serovars was identified. The serovar patterns for men and women patients were very similar, except for one WII/III serovar that was 10 times more common in isolates from men than from women. Most isolates from different anatomical sites in the same patient were of the same serogroup and serovar. Two double infections were found. One patient had a genital infection with serogroup WII/III and a rectal infection with serogroup WI. Another patient with genital, rectal, and throat infections with serogroup WI was found to have gonococci of different GS serovars at each site. It was concluded that the level of discrimination achieved with the monoclonal antibody reagents should prove to be valuable in studying the micro epidemiology of gonococcal infection.